Faktor–Faktor Resiko Yang Berhubungan Dengan Kejadian Skizofrenia Di Rumah Sakit Jiwa Tampan Pekanbaru - Chairil; Intan (LPPM Universitas Muhammadiyah Riau, 2021)
Background: Schizophrenia is a type of serious mental illness or disorder or chronic mental disorder that can reduce the quality of human life. The incidence of schizophrenia in the Tampan Pekanbaru Mental Hospital was 448 cases in 2020. The purpose of this study was to identify and explain the most influential risk factors for the incidence of schizophrenia at the Tampan Pekanbaru Mental Hospital.Methods: This type of research is analytic observational with a case control approach with a total sample of 52 cases and 52 controls. Case and control sampling technique used simple random sampling. Analysis of the data used is univariate analysis, bivariate using Chi Square test, the study was carried out on February 12 to March 16, 2020. Results: The risk factors associated with the incidence of schizophrenia at the Tampan Pekanbaru Mental Hospital are family history (p=0.010; aOR=3,068 95%CI=1,371–6,869). While the variables that are not related to the incidence of schizophrenia are work history, marital status (p= 0,228; aOR= 1,716 95%CI = 0,803 – 3,668).